Child and adolescent social withdrawal predict adult psychosocial adjustment: A meta-analysis - Gazelle, Heidi; Shafer Lundin, Jessie K.; Lei, Haochen; Cao, Hongyuan; Litchfield, Meghan (Frontiers in Developmental Psychology, 2024)
This systematic review and set of five meta-analyses synthesized the results of prospective longitudinal publications on childhood and/or adolescent social withdrawal as a predictor of adult psychosocial adjustment. Meta-analyses were conducted with results for five adult outcomes from a pool of 31 publications derived from 14 longitudinal samples and a combined sample size of 19,806 adults (50% women, M = 38.88 years, 83% White) with childhood and/or adolescent (≤ 16 years) histories of social withdrawal and their offspring (N = 175). Dependency among publications derived from the same longitudinal samples was explicitly modeled in meta-analyses with clustering. Metaanalytic results support childhood and/or adolescent social withdrawal as a medium-sized risk factor for adult social anxiety and intergenerational difficulties in mothers and their offspring (both p < .0001); a small-size risk factor for delayed adult developmental milestones (p < .05), adult social withdrawal (p < .0001), other anxiety (p < .05), and depression (p < .01); and a small-size protective factor against adult substance use (p < .01). However, meta-analytic results did not support childhood and/or adolescent social withdrawal as a predictor of physical health, likely due to the heterogeneous nature of the investigated health outcomes. Consistent with a Developmental Science Model, results are interpreted as supporting interpersonal mechanisms (missing out, interpersonal stress, and poor relationship quality) and developmental cascades (cross domain-influences) in socially withdrawn children's life-course development. Because evidence for intergenerational difficulties was based on a single longitudinal sample, confidence in intergenerational effects would be increased by replication in other samples. Heterogeneity among effect sizes included in most meta-analyses suggests that the relation between childhood and/or adolescent social withdrawal and adult outcomes is likely to be moderated by other factors. Future directions in this area of research are discussed.